An AFLP diversity study of the genus Passiflora focusing on subgenus Tacsonia - Segura, Sergio D.; Coppens d'Eeckenbrugge, Geo; Bohórquez Cháux, Adriana; Ollitrault, P; Tohme, Joseph M. (Springer, 2002)
DNA variation was studied at the intra- andinterspecific levels within the genus Passiflora, with particular emphasis on the subgenusTacsonia and its relationship with the subgenusPassiflora. AFLP fingerprints were generated for35 accessions from 21 species, 14 of which belong to subgenusTacsonia, and four to subgenusPassiflora. The morphologically intermediateP. manicata (subgenusManicata) was also included, as wereP. trinervia (subgenusPsylanthus) and P.alnifolia (subgenus Decaloba). The two latter were used as outgroup species. Twoprimer combinations generated 34–80 scorable fragments pergenotype for a total of 260 fragments. Polymorphism analyses spannedthe levels from individual genotype to section. SubgenusTacsonia presented wide genetic variability atboth intra- and interspecific levels, particularly within wildspecies. The classification based on these markers generally agreeswell with current taxonomic definitions of common species, but lesswith definitions of sections. A geographical component was evident inthe intraspecific variation of P.mixta, P.tripartita var. mollissimaand P. tarminiana, withwider variation in Ecuador and Peru than in Colombia and Venezuela.These same three species, plus P.cumbalensis, formed adjacent clusters, showingcloser affinity with each other than with the other species ofsubgenus Tacsonia. As expected, P. manicata clustered at anintermediate position between subgenera Tacsoniaand Passiflora.